Enterocutaneous fistula from a perforated incarcerated Littre inguinal hernia in an infant - Shubham Gupta; Maneesh Kumar Joleya; Shashi Shankar Sharma; Brijesh Kumar Lahoti; Ashok Laddha; Ram Mohan Shukla; Pooja Tiwari; Vinod Raj (Elsevier, 2022)
Introduction: Inguinal hernia is a common surgical condition encountered of pediatric age group. Inguinal hernia may get incarcerated and if strangulated, it requires prompt intervention. Rarely incarcerated bowel can perforate leading to formation of entero-cutaneous fistula. Littre's hernia is the protrusion of a Meckel diverticulum through a potential abdominal opening. Presentation of case: A one and half months old infant presented with an irreducible right inguino-scrotal swelling and faecal discharge from the scrotum for a month. Patient was passing stools from normal anal opening as well. Patient underwent exploratory laparotomy which revealed an incarcerated right inguinal hernia containing long ruptured Meckel's diverticulum of size 8 cm passing from deep inguinal ring to right hemiscrotum. Diverticulectomy with ileo-ileal end to end anastomosis with right herniotomy was done. Discussion: The main complication of inguinal hernia is incarceration, which may result in bowel obstruction. Spontaneous intestinal-cutaneous fistula from incarcerated inguinal hernia with Meckel's diverticulum as content in neonates and infants is a rare occurrence and hitherto only one such case has been reported in the world literature. Conclusion: Prompt and early seeking of medical facility of patients with incarcerated inguinal hernias is necessary to reduce their morbidity and mortality.